Performance, evaluation, and enhancement of red sand for road bases, embankments, and seawall fills - Jitsangiam, Peerapong (Curtin University, 2007)
Australia produces approximately 40% of the world’s bauxite and over 30% of the world’s alumina. Each year, about 25 million tonnes of bauxite residue is produced in Australia, requiring storage and maintenance. The construction and operation of such large impoundment areas is costly. During the extraction of alumina from bauxite ore using the Bayer process, a fine residue is produced called Red Mud. In West Australia, Darling Range bauxite deposits contain high levels of quartz which result in a coarse residue fraction also being produced. This fraction has been termed Red Sand with a typical particle size in excess of 90 microns. Typically, red mud and red sand are produced in almost equal quantity. Processing of red sand can neutralise the residual caustic and lower the salt content as required. Magnetic separation is also possible to produce a high silica fraction having low iron oxide content. The sustainable use of coarse bauxite residues for road construction is an attractive option with a high potential for large volume reuse.This study focuses on whether red sand is a viable option for use as a road base, embankment fills and as seawall fills in Western Australia. Red sand comes from bauxite ore, a product of intense tropical weathering. Hence, there are various physical properties resulting from the weathering process. Thus it is necessary to fully understand the characterisation of red sand with respect to its engineering properties in the initial part of this research. To satisfy minimum requirements of road bases, a soil stabilisation technique (a Pozzolanic- Stabilised Mixture, PSM) was used. The intent of this stabilisation technique was to use Western Australia’s by-products as stabilising materials. A Pozzolanic - Stabilised Mixture consisting of Class F fly ash (a by-product from a coal power station) and activators (the byproduct from the quicklime manufacturing in terms of lime kiln dust) were employed to develop pozzolanic activity. Once the appropriate mixture of red sand, fly ash, and activators was established (based on a maximum dry density and a value of unconfined compressive strength), a set of laboratory tests were performed which included a triaxial compressive strength test, a resilient modulus test, and a permanent deformation test.Comparisons were made between the stabilised red sand and the conventional road base material in Western Australia (crushed rock added with 2% General Purpose (GP) Portland Cement named Hydrated Cemented Treated Crushed Rock Base, HCTCRB). As for the use of red sand for embankments, the representative stabilised red sand (from red sand for road bases) was used to be an alternative fill embankment material. A testing program to evaluate the important properties of stabilised red sand for embankments including permeability, compressibility and strength was undertaken. The permeability, compressibility, and strength of the representative type of red sand were examined to assess the suitability of red sand as seawall fill. The application of red sand and stabilised red sand on three structures (road bases, embankments and seawalls) is also discussed.